การกำหนดตำแหน่งการจัดเก็บสินค้าโดยพิจารณาเวลาและ ความถี่สำหรับการเข้าสู่พื้นที่ช่องจัดเก็บสินค้า - ธนัช จิราตระกาล (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This research presents a mathematical model for product storage assignment considering two objectives that are to minimize total traveling time and congestion in storage area. Numerical example problems with different in the number of storage blocks and product types were solved to demonstrate how the proposed model and procedure work. Firstly, considering a small-size test problem, the mathematical model was formulated and the optimal solution of each objective function was solved using the exact algorithm via LINGO. Then two objectives were combined using Weight Normalization technique to present the compromise solution and the solution was verified by checking the problem’s constraints. The exact algorithm cannot present the optimal solution when the size of problem is increased, one meta-heuristic method, GLN-PSO, was applied together with the Pareto technique for finding the compromise solution of the two objectives. Then the solutions were compared with the previous research, Pongsakorn Meesuk (2014), that considered only minimizing the total traveling distance. The comparison with the previous research presented that the proposed method yield better performance in terms of total time and congestion when the total traveling distance was greater than the previous research about 5%.